Analisis Faktor-Faktor Yang Mempengaruhi Produksi Usahatani Padi Sawah Varietas Inpari 45 - Baihaqi syahputra; M. Nasir Ismail; Syarifuddin Syarifuddin; Teuku Fadhla (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
Farming is a science that studies how a person allocates existing resources effectively and efficiently to obtain high profits at a certain time. The aim of this research is to determine the effect of land area, seeds, labor, urea fertilizer, NPK fertilizer, TSP fertilizer and pesticides on the production of lowland rice of the Inpari 45 variety in Lam Seunong Cot Keueung Village, Kuta Baro District, Aceh Besar Regency. The research method used was a survey method. The sampling technique